Spectrophotometric Estimation of Cefprozil Sulphate in Pharmaceutical Formulations - Appala Raju, N.; Venkateswara Rao, J.; Vanitha Prakash, K.; Mukkanti, K. (Asian Journal of Chemistry, 2010)
Three simple, accurate, rapid and sensitive methods (A, B and C) have been developed for estimation of cefprozil sulphate in its pharmaceutical dosage form. The method A is based on reaction of cefprozil with ferric chloride and 1,10- phenanthroline to form a blood red coloured chromogen. The method B is based on reaction of cefprozil with ferric chloride 2,2'-bipyridyl to form blood red coloured chromogen. The method C is based on the reduction of ferric ions of the reagent ferric chloride to ferrous ions by the drug, which further in the presence of potassium ferricyanide produces blue coloured chromogen. These methods exhibit maximum absorption at 510, 520 and 720 nm, respectively and obey the Beer's law in the concentration range of 5-30, 5-50 and 1-10 mcg/mL, respectively. The methods have been statistically evaluated and were found to be precise and accurate. The proposed methods are economical and sensitive for estimation of cefprozil sulphate in bulk drug and in its formulations.